IMPLEMENTASI MULTI DATABASE SEKMA PADA INFRASTUKTUR BERBASIS MICROSERVICE - Andre Pratama Adiwijaya (Jurnal Teknik dan Science, 2022)
Currently the development of infrastructure is quite fast which must support business performance in a company. Infrastructure technology itself has several licenses such as monolid and microservice. The microservice scheme by using OKD we can produce multiservice applications where there are problems in the service this service will not interfere with other services. Due to the process within the microsoft itself stands alone, to integrate services one by one can use config files from the microservice side. In OKD itself there is already a tool to monitor each service such as monitoring logs, YAML configuration and others. In this research, the application was monitored actively and successfully up to the time. If there is a problem with the service, OKD will provide a warning on the dashboard.